The Appearance of Accountability: Communication Technologies and Power Asymmetries in Humanitarian Aid and Disaster Recovery - Madianou, Mirca; Ong, Jonathan Corpus; Longboan, Liezel; Cornelio, Jayeel S. (Journal of Communication, 2016)
New communication technologies are celebrated for their potential to i mprove the accountability of humanitarian agencies. The response to Ty phoon Haiyan in 2013 represents the most systematic implementation of “accountability to affected people” initiatives. Drawing on a year-lon g ethnography of the Haiyan recovery and 139 interviews with humanitar ian workers and affected people, the article reveals a narrow interpre tation of accountability as feedback that is increasingly captured thr ough mobile phones. We observe that the digitized collection of feedba ck is not fed back to disaster-affected communities, but is directed t o donors as evidence of “impact.” Rather than improving accountability to affected people, digitized feedback mechanisms sustained humanitar ianism's power asymmetries.
Keywords: Accountability; Audit; Communication for Development; Disasters; Ethnography; ICT4D; Mobile phones; Participatory Communication; SMS; Texting; humanitarianism